Reduced Instruction Set Computers Then and Now. - Patterson, David (Computer (00189162), 2017)
A widely cited Computer article published in 1982 described the reduced instruction set computer (RISC) as an alternative to the general trend at the time toward increasingly complex instruction sets. A RISC executes most instructions in a single short cycle.